PENGARUH LITERASI KEUANGAN DAN DIGITALISASI TERHADAP KINERJA UMKM SONGKOK RECCA DI KABUPATEN BONE - Sitti Hardiyanti; Wilda Wilda; Sari Ekawati (Universitas Ichsan Sidenreng Rappang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) producing Songkok Recca, a traditional Bugis handicraft in Bone Regency, represent a culturally based industry with considerable economic potential. However, these enterprises continue to face challenges related to financial literacy and the adoption of digital technology. This study aims to examine the effects of financial literacy and digitalization on the performance of Songkok Recca MSMEs in Bone Regency, both partially and simultaneously. The study employed a quantitative approach with a causal-comparative research design, involving 30 MSME owners selected through simple random sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics Version 26. The findings indicate that financial literacy has a positive and statistically significant effect on MSME performance (t = 3.939; p = 0.001), whereas digitalization has a positive but statistically insignificant effect (t = 0.532; p = 0.599). Simultaneously, financial literacy and digitalization have a positive and statistically significant effect on MSME performance (F = 32.334; p < 0.001), with a coefficient of determination (R²) of 0.705. These findings suggest that improving financial literacy is the primary factor in enhancing the performance of Songkok Recca MSMEs, while greater optimization of digitalization should continue to be encouraged to strengthen business competitiveness and long-term sustainability.